Current Trends in the Development of EGFR Inhibitors as Promising Anticancer Agents: Sar and Synthetic Studies from (2010-2020) - Mondal, Sitanshu; S., Vishakha; Kajal, Kumari D.; Wahan, Simranpreet K.; Kurmi, Balak Das; Patel, Preeti (Current Organic Chemistry, 2023)
The EGFR (Epidermal Growth Factor Receptor) regulates cell proliferation, survival, and differentiation. The EGFR is a cell surface receptor that belongs to the ErbB tyrosine kinase family. One of the most important targets for cancer therapy is EGFR inhibition. Because EGFR over-activation is seen in a wide range of malignancies, targeting EGFR and its downstream signaling cascades is a sensible and beneficial strategy in cancer therapy. This review highlighted the most potent EGFR inhibitors with SAR studies and their synthetic chemical pathways discovered between 2010-2020, employed for treating Liver, Breast, Lung, Pancreatic, and Colorectal cancers. We also include the clinical trials and the registered patents in our review.
Keywords: EGFR inhibitors